Bright room temperature single photon source at telecom range in cubic silicon carbide - Wang, Junfeng; Zhou, Yu; Wang, Ziyu; Rasmita, Abdullah; Yang, Jianqun; Li, Xingji; von Bardeleben, Hans Jürgen; Gao, Weibo (Nature communications, 2018)
Single-photon emitters (SPEs) play an important role in a number of quantum information tasks such as quantum key distributions. In these protocols, telecom wavelength photons are desired due to their low transmission loss in optical fibers. In this paper, we present a study of bright single-photon emitters in cubic silicon carbide (3C-SiC) emitting in the telecom range. We find that these emitters are photostable and bright at room temperature with a count rate of ~ MHz. Altogether with the fact that SiC is a growth and fabrication-friendly material, our result may be relevant for future applications in quantum communication technology. Room-temperature solid-state single photon emitters in the telecom range are suitable for quantum communication. Here, the authors observe defects in high-purity 3C-SiC epitaxy layers grown on a silicon substrate, with good characteristics in terms of brightness, emission’s polarization and photostability.